The functions of human saliva: A review sponsored by the World Workshop on Oral Medicine VI. Issue 6 (June 2015) - Dawes, C.; Pedersen, A.M.L.; Villa, A.; Ekström, J.; Proctor, G.B.; Vissink, A.; Aframian, D.; McGowan, R.; Aliko, A.; Narayana, N.; Sia, Y.W.; Joshi, R.K.; et al.
Highlights A narrative review was carried out of the functions of human saliva. Saliva moistens and lubricates the mouth and is important for taste and smell. Saliva protects the teeth and the oral and oesophageal mucosa in many ways. Saliva has antibacterial and wound healing properties.